Revision External Dacryocystorhinostomy Results After a Failed Dacryocystorhinostomy Surgery. Issue 1 (June 2016) - Akcay, Emine; Yuksel, Nilay; Ozen, Umut
Abstract Objective To report revision external dacryocystorhinostomy (rE-DCR) results following failed dacryocystorhinostomy (DCR) surgery. Methods A retrospective review of patients who underwent rE-DCR between June 2006 and June 2015 at Yıldırım Beyazıt University Ankara Ataturk Training and Research Hospital Department of Ophthalmology. Data were collected on the primary surgery technique and patient demographics. Results Forty-one rE-DCRs were performed on 40 patients after various failed DCR techniques. Two patients had failed DCR twice, and 38 patients had failed DCR once. Six of these previous failed DCRs were multidiode laser DCR, two of them were endoscopic DCR, and 33 were external dacryocystorhinostomy (E-DCR). In all rE-DCR procedures, silicone tube intubation was performed, and the tube was removed at least 6 months after surgery. We used mitomycin C on 16 patients (40%). At the last examination, six patients still had epiphora (15%), and their nasolacrimal passage was obstructed. Thirty-four patients had no complaints, and their passages were open (85%). Conclusion The rE-DCR procedure has high success rates for failed DCR surgeries, whichever procedure was performed.